1983
DOI: 10.1271/bbb1961.47.1647
|View full text |Cite
|
Sign up to set email alerts
|

Further characterization of C6-aldehyde-forming system in alfalfa cells cultured in vitro.

Abstract: VolatileC6-aldehydes such as hexanal, m-3-hexenal and Jrarcs-2-hexenal, along with the corresponding alcohols, characterize flavors of plant tissues and are found in a variety of plants.1} Lipoxygenase and hydroperoxide lyase (HPO lyase) are responsible for the enzymatic formation of these C6-aldehydes from linoleic and linolenic acids originating from lipids.2) In a previous paper we reported that cultured green cells of alfalfa had the ability to produce the C6-aldehydes from linoleic and linolenic acids.3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
1
1
0
Order By: Relevance
“…A direct correlation of C6-aldehyde forming activities and chlorophyll content was demonstrated by the same authors [5,14]. These observations may be generalized with respect to results with white and green calli of apple cv.…”
Section: Resultssupporting
confidence: 58%
“…A direct correlation of C6-aldehyde forming activities and chlorophyll content was demonstrated by the same authors [5,14]. These observations may be generalized with respect to results with white and green calli of apple cv.…”
Section: Resultssupporting
confidence: 58%
“…Sekiya et al (1983a) reported a positive correlation between HL activity and chlorophyll content in the green leaves of various plants, but LOX activity seemed to affect the production of C 6 aldehydes. LOX activity of cultured green alfalfa cells is lightdependent, but HL activity is only slightly light-dependent (Sekiya et al, 1983b). Sekiya et al (1984) demonstrated that LOX activity is higher at higher temperatures in tea leaves, and ADH activity was low at high temperature.…”
Section: Feasibility Of Using Independent Volatile and Biomass Datamentioning
confidence: 99%